DEVELOPMENT OF ARTISTIC AND CREATIVE SKILLS IN PRIMARY SCHOOL CHILDREN USING WATERCOLOR PAINTING - Jennet Gurbannepesova (American Journals Publishing, 2025)
This article examines the development of artistic and creative skills in primary school children through watercolor painting. It analyzes the specific perceptions of color, form, and space in children of this age group, revealing the pedagogical potential of watercolor as an expressive and accessible artistic medium. Particular attention is paid to methodological approaches to developing creative thinking and aesthetic perception.
Keywords: Artistic and creative skills, primary school age, watercolor painting, art education, visual arts.